Achieving visible and near-infrared dual-emitting mechanoluminescence in Mn2+ single-doped magnesium aluminate spinel. Issue 32 (28th July 2022) - Wang, Tianli; Liu, Fei; Wang, Ziqi; Zhang, Jia; Yu, Shuaishuai; Wu, Junxiao; Huang, Jiahao; Wang, Wenjie; Zhao, Lei
Abstract : In this work, the self-recovered visible-NIR dual-emitting ML material MgAl2 O4 :Mn 2+ was successfully developed. Thus, the application potential in electronic signature, multiple security and information encryption is improved. Abstract : Visible (VIS) and near-infrared (NIR) mechanoluminescence (ML) materials have been developed rapidly for use in energy conversion, biological applications and mechanical sensing. The realization of visible and NIR ML in single host materials meets the dual requirements of visualization and anti-interference for high-precision mechanical sensing. In this work, Mn 2+ single-doped magnesium aluminate spinel MgAl2 O4 with excellent ML performance was studied in detail. Bright, visible green and NIR ML were achieved under mechanical stimulation, and the ratio between visible and NIR ML intensity can be regulated by manipulating the doping concentration of Mn 2+ . The generation of ML without additional pre-irradiation proved that the self-powered ML phenomenon was independent of trap. The functional relationship between mechanical parameters and ML intensity indicated that the doped spinel can be used for visualization, anti-interference and non-contact mechanical sensing. In addition, the NIR ML of MgAl2 O4 :Mn 2+, centered at 835 nm, is located in the first NIR window (NIR-I, 650–950 nm), which effectively penetrates living tissue such as skin, fat, and lean meat, respectively, showing that it has potential applications in in vivo optical imaging.